2009
DOI: 10.1093/hmg/ddp521
|View full text |Cite
|
Sign up to set email alerts
|

Novel sequence feature variant type analysis of the HLA genetic association in systemic sclerosis

Abstract: We describe a novel approach to genetic association analyses with proteins sub-divided into biologically relevant smaller sequence features (SFs), and their variant types (VTs). SFVT analyses are particularly informative for study of highly polymorphic proteins such as the human leukocyte antigen (HLA), given the nature of its genetic variation: the high level of polymorphism, the pattern of amino acid variability, and that most HLA variation occurs at functionally important sites, as well as its known role in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 33 publications
1
38
0
Order By: Relevance
“…When evidence of strong balancing selection is seen at a number of AA sites (Salamon et al 1999;Valdes et al 1999;Lancaster 2006), how does one determine which AA sites could potentially show independent evolution vs. correlation due to high LD? Similarly with disease-association studies of individual AAs and biologically relevant sequence features (SFs) and their variant types (VTs) (Karp et al 2010;Thomson et al 2010), how can one distinguish between potentially causal effects vs. those due to LD? These AA-level analyses showed that there are cases with different numbers of "alleles" (AAs or SFVTs) at two loci where W n = 1; nonetheless a stratified analysis could be applied to potentially distinguish disease predisposing variants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When evidence of strong balancing selection is seen at a number of AA sites (Salamon et al 1999;Valdes et al 1999;Lancaster 2006), how does one determine which AA sites could potentially show independent evolution vs. correlation due to high LD? Similarly with disease-association studies of individual AAs and biologically relevant sequence features (SFs) and their variant types (VTs) (Karp et al 2010;Thomson et al 2010), how can one distinguish between potentially causal effects vs. those due to LD? These AA-level analyses showed that there are cases with different numbers of "alleles" (AAs or SFVTs) at two loci where W n = 1; nonetheless a stratified analysis could be applied to potentially distinguish disease predisposing variants.…”
Section: Discussionmentioning
confidence: 99%
“…Amino-acid position 13 (AA13) of DRB1 shows the strongest single AA association with JIA-OP. This association is also stronger than other potentially biologically relevant combinations of AAs defined under sequence feature variant-type (SFVT) analysis (Karp et al 2010;Thomson et al 2010). AA13 is also identified as potentially causative in disease using an extension of Salamon's unique combinations algorithm (Salamon et al 1996;Thomson et al 2010).…”
Section: Hla Disease Association Datamentioning
confidence: 91%
“…In the case of autoimmune diseases, several allelic associations have been established – e.g. HLA-B*2705/2/4/7 with ankylosing spondylitis, HLA-DRB1*0401/*0404/*0405 with rheumatoid arthritis, HLA-DR3, -DQ2 and -C4AQ0 with systemic lupus erythematosus, and HLA-DR3, -DR11 and -DR7 with systemic sclerosis [19,20]. Pericarditis is also associated more or less frequently with autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%
“…An exciting and novel approach to the study of associations with the HLA region variables in SSc was described by Karp et al [11]. They subdivided proteins codified by HLA-DRB1 into biologically relevant smaller sequences features (SFs) and their variant types (VTs), and analyzed the combinations of variable amino acid sites shared by several HLA alleles to evaluate which were most likely to describe the causative genetic variants.…”
Section: Hlamentioning
confidence: 99%